Why do currency black markets exist? - Pshenychna, A. (ТДАТУ, 2018)
The existence of substantial demand on currencies is caused when people look at currency as a way of saving their cash values. The state control makes it extremely difficult for citizens to buy foreign currencies with their local currency at the official exchange rate. A black market, therefore, develops for foreign currencies that would generally be priced at a significant premium to the official exchange rate, because of its artificial value and the demand-supply imbalance
Keywords: currency; market; cash transactions; underground economy